New crustal models of Drake Passage and the hydrocarbon reservoir searching in the Antarctic Peninsula continental margin structures (by the 17th Ukrainian Antarctic Expedition results) - Korchagin, I.N.; Solovyov, V.D.; Bakhmutov, V.G.; Levashov, S.P.; Yakymchuk, N.A.; Bozhezha, D.N. (Український антарктичний журнал, 2013)
During the 17th Ukrainian Antarctic Expedition (UAE, 2012) new geophysical data for the West Antarctica bottom structures were obtained. The geophysical investigations included the geoelectric methods of forming a short-pulsed electromagnetic field (FSPEF), vertical electric-resonance sounding (VERS) and the special method of remote sensing (RS) satellite data processing and interpretation. These methods were used for the crustal structure studying and the hydrocarbon accumulations searching in continental margin bottom structures. Detailed geoelectric sections (with depth up to 24km) were constructed for Drake Passage, Scotia Sea and Bransfield Strait tectonic structures as a result of these seasonal works. There are presented some crustal boundaries between stratigraphically heterogeneous layers and deep depth discontinuities. The occurrence of complex fault zones near the coast of South America and the Antarctic Peninsula are showing.Some specific geoelectric boundaries below the Moho presence and the occu rrence of possible deep hightemperature zones of rocks may reflect the heterogeneity of Passage bottom structures and available processes of tectonic and magmatic activity with the local areas of modern rifting. Представлены результаты геоэлектрических исследований глубинного строения земной коры (до 24 км) пролива Дрейка, а также новые данные об углеводородном потенциале структур материковой окраины Антарктического полуострова, полученные во время сезонных работ 17-й УАЭ (март 2012 г.). Морские геоэлектрические методы СКИП и ВЭРЗ применялись в комплексе с новой технологией обработки и дешифрирования спутниковых данных дистанционного зондирования Земли, что позволило провести «прямые» поиски углеводородов в рамках «вещественной» парадигмы интерпретации геофизических данных. Представлено нові результати геоелектричних досліджень глибинної будови земної кори (до 24 км) протоки Дрейка, а також нові дані про вуглеводневий потенціал структур материкової окраїни Антарктичного півострова, отримані під час проведення сезонних робіт 17-ї УАЕ (березень 2012 р.). Морські геоелектричні методи СКІП і ВЕРЗ застосовувалися в комплексі з новою технологією обробки і дешифрування супутникових даних дистанційного зондування Землі, що дозволило провести «прямі» пошуки вуглеводнів у рамках «речової» парадигми інтерпретації геофізичних даних.